Perception and level of soil and water conservation practices adoption by farmers in a watershed - Rodrigues de Melo, Thadeu; Augusto Asai, Guilherme; Eiji Higashi, Gabriel; Lúcia Londero, Ana; Moraes de Cesare Barbosa, Graziela; Santos Telles, Tiago (Revista Ciência Agronômica, 2022)
In Brazil, to conserve soil and water, the adoption of a complete array of conservation agriculture technologies in conjunction with contour farming and agricultural terraces is necessary. However, there is little knowledge about the awareness and adoption level of conservationist practices by farmers. In this context, the objective of the study, which took place in a watershed containing agricultural areas dominated by annual crops, was to verify farmers’ perception and adoption level of soil and water conservation practices and the relationship between their adoption level of conservation practices and their socioeconomic characteristics. For this purpose, a survey was carried out with farmers in the Rio Vermelho watershed in southern Brazil. It was found that the majority of farmers have adequate awareness about the use of soil and water conservation practices. Maintaining productivity was identified as the main reason to conserve soil and water, while reducing production costs and controlling erosion stood out as secondary reasons. Agricultural terraces and no-tillage were the most adopted practices by farmers. No-tillage was implemented by approximately 78.3% of landowners and 50% of tenants. However, only 26.8% of farmers adopted conservation agriculture. Overall, most farmers adopt conservationist practices, but in a partial manner, which may not be sufficient to ensure soil and water conservation. Awareness of soil and water conservation needs to be further improved.